Scrotal Kaposi Sarcoma in a HIV-Negative elderly Nigerian. A case report with a review of literature. (Journal of Current Biomedical Research, 2023)
Kaposi Sarcoma KS is a rare, borderline vascular tumour that affects themucocutanous surfaces, and lymph nodes and visceral organs occasionally. Variousforms have been described with a common association with Herpes Simplex virus 8infection, although immunological, environmental andKaposi Sarcoma KS is a rare, borderline vascular tumor that affects the muco-cutanous surfaces, and lymph nodes and visceral organs occasionally. Various forms have been described with a common association with Herpes Simplex virus 8 infection, although immunological, environmental and genetic factors play significant role in its pathogenesis. Urogenital involvement is uncommon and isolated scrotal KS in HIV negative individuals is extremely rare. We therefore report the 5th of such case in English literature, involving a 65 year old Nigerian, with confirmed histological and immunohistochemistry diagnostic features. Patient underwent surgical excision of the lesion and is being considered for chemotherapy.genetic factors play significantrole in its pathogenesis. Urogenital involvement is uncommon and isolated scrotal KSin HIV negative individuals is extremely rare. We therefore report the 5th of such casein English literature, involving a 65 year old Nigerian, with confirmed histologicaland immunohistochemistry diagnostic features. Patient underwent surgical excision ofthe lesion and is being considered for chemotherapy.
Keywords: HIV-Negative; Kaposi Sarcoma; Nigerian